Major histocompatibility complex and mate choice in the polygynous primate: the Sichuan snub‐nosed monkey (Rhinopithecus roxellana). Issue 5 (November 2014) - YANG, Banghe; REN, Baoping; XIANG, Zuofu; YANG, Jingyuan; YAO, Hui; GARBER, Paul A.; LI, Ming
Abstract The highly polymorphic genes within the major histocompatibility complex (MHC) not only play a major role in immunity resistance, but also seem to provide hints for mate choice in some animal populations. In the present study we investigated MHC‐related mate choice in a small natural population (group size 40–55 individuals) of a polygynous primate, the Sichuan snub‐nosed monkey (Rhinopithecus roxellana). We found that there was no evidence either for MHC‐disassortative mating, or for females to mate with males based on MHC heterozygosity or specific alleles. Nevertheless, of the 11 alleles identified, we found that the frequencies of 2 alleles, Rhro‐DRB2 (P < 0.01) and Rhro‐DRB5 (P < 0.05) were higher in offspring than in their parents. These findings suggest that MHC‐DRB in this population of R. roxellana is unlikely to be associated with mating preferences. Limited female opportunities for mate choice are likely due, in part, to the harem breeding structure present in R. roxellana, and the relatively small number of resident adult males in our study band (N = 4–6). In addition, we suggest that differences in the frequency of particular alleles across generations may be linked to parasite resistance in a fluctuating environment; however, confirmation of this finding requires further study.